Sistem Pengelolaan Parkir dengan NFC - Bayu Widyo Harimurti; Wijaya Kurniawan; Heru Nurwasito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Parking is the process of every vehicle that stops at certain places whether expressed by signs or not, and not solely for the benefit of raising or lowering people or goods. Research this discusses how to accelerate the parking process using client server method where. Users only match the data that is embedded in the system with the user id. Connected system capable of displaying real time information that updates quickly for users of both the student and admin users. Which involves human and machine relationships to support the running of the system in order to manage well within the organization. NFC is a series of wireless technology at close range, which requires a distance less than 10 cm or less. Website there is maping the parking area and the capacity that updates in real time. With the speed of registration system (check in, check out) faster. Because the RFID reader reads the NFC Tag in seconds. While the NFC Tag is owned only 1 unit for 1 student, which is given by the Admin. NFC Tags are not easy to forge. Because each Tag has a different ID, and if it is falsified. Fake Tags can not be synchronized with the data on the server, because the fake id is indeed not listed.